EXAMINATION OF NURSING STUDENTS' ACCEPTANCE LEVELS FOR AESTHETIC SURGERY AND AFFECTING FACTORS - Altun Baksi (Rojan GÜMÜŞ, 2021)
As a result of the rise of socioeconomic levels and globalization in the 21st century, aesthetic appearance has become more prominent, and the aesthetic/cosmetic sector has made great progress. Nursing education and practice are constantly evolving to meet the needs of the current community. The aim of this research is to examine the acceptance level of nursing students for aesthetic/cosmetic surgery and the affecting factors. This research is of descriptive type. It was conducted in the nursing department of a university in western Turkey (n:179). Permission was obtained from authors who made the adaptation of the scale used in this research, ethics board, institution, and students. The research data were collected using the introductory information form and Cosmetic Surgery Acceptance Scale (CSAS). Number, percentage, mean, standard deviation, Pearson correlation analysis, t test, Mann Whitney u test, one-way Anova and Kruskal Wallis test were used to evaluate the data. 84.9% of nursing students were women, 58.1% had income equal to expenses, 23.5% had a father with undergraduate or higher degree, and 49.2% lived in the city center before enrolling in university. 2.8% of students had previous experience of aesthetic surgery, 29.1% had a friend/family member undergoing aesthetic surgery earlier, 44.7% stated that those who underwent aesthetic surgery were stigmatized by the community, 48.6% stated that aesthetic surgery was not risky compared to other surgical procedures, 55.3% stated that they wanted awareness training about aesthetic surgery, and 47.5% stated that individuals underwent aesthetic surgery to become more beautiful. The mean CSAS score of nursing students was 56.11±21.80 (16.00-105.00). When looking at the characteristics that may affect acceptance levels of the students for aesthetic surgery, there was a statistically significant difference in terms of having a father with undergraduate degree or higher education, living in the city center before enrollment at university, having a friend/family member with previous aesthetic surgery, not seeing aesthetic surgery procedures as more risky compared to surgical procedures and seeking awareness training related to aesthetic surgery. Aesthetic surgery acceptance level of nursing students was found to be moderate. The interaction of demographic and socio-cultural factors plays a role in accepting aesthetic surgery.